2020
DOI: 10.1137/19m1296355
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Order Model Approach to Inverse Scattering

Abstract: We study an inverse scattering problem for a generic hyperbolic system of equations with an unknown coefficient called the reflectivity. The solution of the system models waves (sound, electromagnetic or elastic), and the reflectivity models unknown scatterers embedded in a smooth and known medium. The inverse problem is to determine the reflectivity from the time resolved scattering matrix (the data) measured by an array of sensors. We introduce a novel inversion method, based on a reduced order model (ROM) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 36 publications
0
45
0
Order By: Relevance
“…To our knowledge, the first sensor array data driven ROM for wave propagation was introduced in [13] for the one-dimensional wave equation. The extension to higher dimensions was obtained in [7] and was analyzed in [8]. The latter study showed that wave propagation can be viewed as a discrete time dynamical system governed by a "propagator operator", where the time step τ is the data sampling interval.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…To our knowledge, the first sensor array data driven ROM for wave propagation was introduced in [13] for the one-dimensional wave equation. The extension to higher dimensions was obtained in [7] and was analyzed in [8]. The latter study showed that wave propagation can be viewed as a discrete time dynamical system governed by a "propagator operator", where the time step τ is the data sampling interval.…”
Section: Introductionmentioning
confidence: 99%
“…The latter study showed that wave propagation can be viewed as a discrete time dynamical system governed by a "propagator operator", where the time step τ is the data sampling interval. This propagator operator maps the wave from the states at instants (j − 1)τ and jτ to the future state at time (j + 1)τ , for any j ∈ N. The ROM in [7,8] is an algebraic analogue of the dynamical system. Its evolution is controlled by an nm × nm propagator matrix, given by the Galerkin projection of the propagator operator on the function space spanned by the first n snapshots of the wave, assuming that the array records for the duration (2n − 1)τ .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations